A new pheretimoid earthworm of the genus Metaphire Sims & Easton, 1972 (Oligochaeta, Megascolecidae) from northeastern China with data from the mitochondrial genome - Huifeng Zhao; Anne Charis N. Han; Min Liu; Yufeng Zhang; Nonillon M. Aspe; Pu Miao; Donghui Wu (Zoosystematics and Evolution)
A new pheretimoid earthworm species, Metaphire liaoningensis sp. nov., was investigated in northeastern China. The taxonomy of M. liaoningensis sp. nov. using morphological characters and molecular data is reported, as well as its current geographical range in northeastern China. The new species, belonging to the M. houlleti species group, is characterized by having three pairs of spermathecal pores in 6/7/8/9, round and small pre-clitellar genital markings medio-ventral to the spermathecal pore opening, the first dorsal pore in 12/13, and the spermathecae ampulla large, nearly elliptical with a surface wrinkled and a duct long and stout. The molecular phylogenetic position of M. liaoningensis sp. nov. within the M. houlleti species group is performed by COI and mitogenomic data, respectively. The COI K2P genetic distance between the new species and the other species within the M. houlleti species group was at least 16%. This is the second updated report of a new pheretimoid species in northeastern China since the last decade.